Development of soil characteristics in the UPN "Veteran" Jawa Timur experimental field in Wonosalam District, Jombang Regency, East Java - Aditya, Haidar Fari; Wijayanti, Fitri (Jurnal Ilmu Pertanian, 2024)
Soil characteristic and properties are essential determinants for effective land management. Soil genesis results from the interaction of various pedogenic factors, which are influenced by environmental conditions, thereby producing diverse soil types in different locations. This study was conducted in the Wonosalam sub-district, an area characterized by diverse regional conditions due to its varied physiographic features. The physiographic and climatic conditions in this region significantly influence soil formation processes. This research focused on monitoring soil development at several locations within Wonosalam, specifically at the UPN "Veteran" Jawa Timur experimental field. The study included five observation points, categorized by land map units: PW1, PW2, PW3, PW4, and PW5. Morphological analyses indicate the presence of two distinct soil types among the five observation points. The soils in PW1, PW2, PW3, and PW4 are classified under the Alfisols order, specifically within the Typic Hapludalf subgroup. In contrast, the soil at PW5 belongs to the Inceptisols order, specifically the Typic Humudepts subgroup. This diversity suggests that the area encompasses soils of different orders. The soil characteristic data obtained from the UPN "Veteran" Jawa Timur experimental field can be utilized as a basis for planning the management of the area.